Effectiveness of an integrated school-based intervention programme in reducing BMI and BMI Z-scores among adolescents in Seremban, Negeri Sembilan, Malaysia - Lai, Wai Kent (2021)
Recent evidence demonstrated substantial rise in the worldwide prevalence of childhood overweight and obesity. However, little is known about the prevalence and its association with socio-demographic, behavioural and psychosocial factors in Malaysia. Furthermore, there’s great potential for schools to develop and encourage healthy lifestyle in students. The objectives of the study were to determine the prevalence and predictors of overweight and obesity among adolescents, and to evaluate the effectiveness of an integrated school-based intervention programme. This study had two phases. Phase one was a cross-sectional study involving 2,221 adolescents who were randomly selected from eight secondary schools in Seremban, Negeri Sembilan. Questionnaire was administered to assess socio-demographic, meal patterns, physical activity level, self-efficacy, self-esteem, body satisfaction, perception of body image and weight management, depression, anxiety, stress and nutrition knowledge. Body weight and height were measured and BMI-for-age z-scores (BAZ) were computed. Multivariable logistic regression was used to test the associations between predictors and the outcome variable. In phase two, an integrated school-based intervention programme was developed based on the predictors and Social Cognitive Theory which focused on knowledge, self-efficacy, goal-setting, self-monitoring, problem solving and relapse prevention. A cluster randomised controlled trial was conducted to evaluate the effect of the intervention consisting of five-session, bi-weekly for 10 weeks (n = 200) and compared with control group (n = 200). The primary outcomes were BMI and BAZ, whereas the secondary outcomes were breakfast consumption, physical activity level, self-efficacy, and body satisfaction which were measured by frequency of breakfast consumption, Physical Activity Questionnaire for Older Children, Healthy Eating and Weight Self-Efficacy scale, Perceived Physical Activity Self-Efficacy Scale for Adolescents and Contour Drawing Rating Scale, respectively. Generalised linear mixed model analysis was used to examine the effectiveness of the intervention at baseline, immediate post-intervention, and 3-month post-intervention, while controlling for covariates. The response rate of phase one was 83.5%. The prevalence of overweight among participants was 17.0%, while the prevalence of obesity was 14.9%. The significant predictors of overweight and obesity were breakfast skipping, low physical activity level, low healthy eating and weight self-efficacy scores, low perceived physical activity self-efficacy scores, body dissatisfaction and perception of large body size. In phase two, the response rate was 80.3%. A significant intervention effect was found in reducing BMI and BAZ. BMI of the participants in the intervention group was reduced from 28.10 kg/m2 to 27.93 kg/m2, and further decreased to 27.80 kg/m2, while BAZ was reduced from 2.19 to 2.12, and further decreased to 2.07, from baseline to immediate post-intervention, and 3-month follow-up, respectively. Furthermore, there was significant improvement in breakfast consumption frequency, physical activity scores, healthy eating and weight self-efficacy scores, perceived physical activity self-efficacy scores, and body discrepancy scores as compared with the control group. The integrated school-based intervention programme was effective in reducing BMI and BAZ among overweight and obese participants. The results suggested that this programme could be integrated as one of the regular school co-curricular programmes.